The Relationship Between the Patient's Personal Assessment of Bruxism and Periodontal Status - Gubayev Mukhitdin Sarimsokovich (Scientific Trends, 2024)
Bruxism is an unconscious recurring episode of masticatory muscle activity, which is not necessarily a disorder in healthy people. There are two forms of Bruxism: wakefulness bruxism and sleep bruxism.